Supportive Communication from Best Friends in Providing Emotional Support for Major Depressive Disorder Patients - Zachrani Kinasih, Audrey Vania; Suciati (Jogjakarta Communication Conference (JCC), 2023)
Supportive communication from best friends plays a role in providing emotional support for patients. This research aims to describe the supportive communication process of best friends toward major depressive disorder patients in an effort to provide emotional support. This research uses a descriptive qualitative approach. The data collection technique used was in-depth interviews. This research applies a purposive sampling technique to get subjects that are in accordance with the research objectives. Meanwhile, the data validity test uses credible subject competence, namely a person with their best friend who is a patient with depressive disorder with a diagnosis from a clinical psychologist or psychiatrist. The results showed that the supportive communication process can take works well because of the supportive behaviors applied in the friendship relationship. However, the best friend informants of partners I and II are not the same in applying supportive behavior. Best friend in the first pair can apply all supportive behaviors to patient, in the form of: description, problem orientation, spontaneity, empathy, equality, and provisionalism. While best friend in pair II apply four supportive behaviors in the form of: problem orientation, spontaneity, empathy and equality.